Language Style Matching in Preschooler–Adult Dyads: Associations with Dyad Familiarity and Children's Age. (October 2019) - Borelli, Jessica L.; Klemfuss, J. Zoe; Hollas, Kristen
Language style matching (LSM) offers promise as an unobtrusive measure of synchrony between members of conversational dyads, but no studies have explored key questions related to LSM in developmental context. We examined LSM in young children's ( N = 87, M age = 54.63 months) interactions with caregivers versus experimenters, and evaluated links between LSM and expressive vocabulary. LSM was significantly higher among caregiver–child than experimenter–child dyads and was positively associated with children's expressive vocabulary.